New human adenovirus associated with respiratory illness: candidate adenovirus type 39. - Hierholzer, J C (1982)
A new human adenovirus was isolated from a stool specimen from a 2-year-old El Salvadorian male hospitalized with severe respiratory illness. The virus, strain D335, is a typical adenovirus by routine classification tests and bears little resemblance to the other 38 adenovirus serotypes by standard hemagglutination inhibition and serum neutralization tests. The only significant cross-reaction observed was between adenovirus types 39 and 13, bilaterally, by the hemagglutination inhibition test. The virus was clearly differentiated from the other human adenoviruses by restriction enzyme analyses with SmaI, SacI, and KpnI enzymes. Strain D335 agglutinates human and rat erythrocytes to moderately high titers and is placed in hemagglutination subgroup 2B on the basis of differential hemagglutination with erythrocytes from 13 animal species. It has a density in cesium chloride of 1.339 g/ml and produces soluble components in human embryonic kidney culture that band at 1.303 g/ml (hexon), 1.283 g/ml (dodecon), and 1.212 g/ml (fiber), the last component being the only incomplete hemagglutinin found. The viral DNA is cleaved into 17 fragments by the SmaI restriction enzyme, indicating that strain D335 is a member of adenovirus subgenus D. Strain D335 is herein described as candidate adenovirus type 39 (Mastadenovirus h 39).